Corie Audette: capstone - Audette, Corie, artist (Colorado State University. Libraries, 2013)
The artist's statement: Once upon a reality, mutant animals inhabited altered environments and dimensions. These animals had foreseen the change coming in sea and land, from which the cause was of the wayward humans' span. In time came life and death, with moments of transition, and from the past wherein they strengthen. The trees and things made by man that once did matter became an icon, lost or forever altered. And through these passages of existences, a world of imaginative meaning did once arrive. My work illustrates narratives of impacting realms through fragments of changing moments and cultural interpretations. I remember the first time I saw the image of Sandy Skoglund's Radioactive Cats and being deeply impacted by it. The piece had an innate notion of conversion that struck me; I wanted to understand and become a part of that world crowded with those mutant cats. I think this is where I was influenced to create art that expressed a serious matter but in an uncanny approach. I am not trying to force a statement about preserving life exactly the way it is now; I know change is inevitable to this world and it happens all the time, but I simply want to preserve these minute moments of transitions by collecting glimpses into possible realities.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.